Optimizing Inclusive Education Through Interactive Learning Modules for Children with Special Needs in Early Childhood: Implications for SDG 4.5 - Mochammad Fadil Djamali; Sugihartatik Sugihartatik; Nova Jessica Vannesa Priska; Indah Kharismawati (Jurnal Ilmiah Profesi Pendidikan, 2026)
This study evaluates the development of an interactive learning module aimed at optimizing inclusive education for children with special needs in early childhood education (ECE), in support of Sustainable Development Goal (SDG) 4.5. Employing a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate), data were collected through curriculum analysis, classroom observations, interviews with teachers and parents, expert validation, teacher practicality questionnaires, and child engagement rubrics, and then analyzed descriptively. The findings indicate that the module was rated “highly valid” by experts with an average score of 89.7%, and “highly practical” by teachers with an average score of 87.5%. Children’s engagement showed a significant increase, rising from 52.8% before to 80.6% after the use of the module, with the greatest improvement observed in social interaction (+29%). These results demonstrate that the UDL-based interactive module is effective in enhancing inclusivity, children’s participation, and teachers’ confidence in inclusive ECE classrooms, thereby contributing to the achievement of SDG 4.5.